Performance of Heat-Stressed Broilers Supplemented with Dietary Choline and Betaine - Kpodo, K.R.; Beckford, R.C.; Smith , M.O. (International Journal of Poultry Science, 2020)
Objective: A study was conducted to determine the effects of supplemental choline (CHO) and betaine (BET) on broiler performance and carcass characteristics under different temperature conditions, thermoneutral (TN: 23.9°C) and heat stress (HS: 28-36°C). Materials and Methods: The corn-soy bean basal (Control) diet was formulated to meet NRC requirements for broilers and supplemented with CHO and BET at 500 or 1000ppm (CHO500, CHO1000, BET500 and BET1000). Feed intake and body weight were recorded weekly by pen. On day 42, foot pads were assessed for health and litter samples collected from each pen. At slaughter on day 52, breast meat was collected for drip loss evaluation at 4 and 7 days post slaughter. Breast meat lightness (L*), redness (a*) and yellowness (b*) were measured. Results: Results showed that HS birds consumed 20.59% less feed and gained 23.34% less weight than TN birds (p<0.05) during 22-49 days of age. The overall feed intake and weight gain during days 1-49 were similarly reduced in HS birds. Heat stress decreased feed efficiency during days 22-49 (p = 0.02). HS birds had lower feed efficiency (0.54) when compared to TN birds (0.56). Drip loss 4 days post slaughter was affected by diet×temperature interaction (p = 0.04) The lowest drip loss occurred with CHO500 (0.60%) in HS and BET1000 (0.83%) in TN birds. Breast meat color of HS birds was lighter (p = 0.02) while that of TN birds was more yellow (p = 0.004). Temperature did not affect pododermatitis (p = 0.22) however, there was an effect of diet (p = 0.003) with CHO500 and BET1000 showing the lowest occurrence of foot pad dermatitis. Conclusion: In this study, breast meat drip loss was influenced by dietary CHO and BET while meat color was affected by rearing temperature. Dietary CHO and BET supplementation did not improve weight loss induced by HS conditions.